Workers' Compensation: Foundations for Reform - Thompson, Mark (Relations industrielles / Industrial Relations, 2002)
The article reviews the book, "Workers Compensation: Foundations for Reform," edited by Morley Gunderson and Douglas Hyatt.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Law; Laws & regulations; Management; Occupational accidents; Reforms; Workers compensation